The role of a local application of 10% doxycycline gel in the prevention of medication-related osteonecrosis of the jaw in rats - Hadad, Henrique [UNESP]; de Jesus, Laís Kawamata [UNESP]; Pereira-Silva, Maísa [UNESP]; Oliveira, Maria Eduarda de Freitas Santana [UNESP]; Monteiro, Naara Gabriela [UNESP]; Poli, Pier Paolo; Maiorana, Carlo; Okamoto, Roberta [UNESP]; Guastaldi, Fernando Pozzi Semeghini; de Almeida, Juliano Milanezi [UNESP]; Souza, Francisley Ávila [UNESP] (Springer Nature, 2025)
Objectives: This study aimed to evaluate doxycycline on the prevention of MRONJ. Materials and methods: Seventy-two Wistar rats were sorted into 3 groups and subjected to tooth extractions. The first group received systemic saline solution (SAL), the second received zoledronic acid (ZA), and the third, besides the systemic ZA, the post-extraction socket received local application of doxycycline (DOXI) gel. Samples were collected and analyzed at 7, 14, and 28 postoperative days. Results: DOXI group presented higher percentage of vital bone area as compared with ZA at 7 (p = 0.0058), 14 (p < 0.0001), and 28 days (p < 0.0001). TRAP immunolabeling was lower in ZA and DOXI at 7 and 14 days, while OCN immunolabeling was similar between the ZA and DOXI, except at 7 days. At 14 and 28 days, DOXI group presented more collagen type 3 and 1 (p < 0.0001) as compared with ZA. RUNX2, ALP, OCN, and RANKL gene expression was downregulated in ZA at 7 days. Conversely, DOXI upregulated these markers and OPG over time (p < 0.05). Conclusion: Doxycycline is an effective local agent for preventing MRONJ, favoring alveolar bone healing. Clinical relevance. Although widely studied, MRONJ remains a significant challenge in dentistry. The search for preventive methods is important to assure safety for in patients under antiresorptive therapy that demand surgical dental treatment. Doxycycline is well-established in dentistry, and the proposal of using this medication as a gel makes it more appealing since it is applied locally and has negligible adverse effects.
Keywords: Antiresorptive drugs; Bisphosphonates; Bone repair; Doxycycline; MRONJ